Pembuatan Website E-commerce dan Pelatihan Digital Marketing untuk Rebranding UMKM Barokah Jaya - Ahmad Faidlon; Shierly Eka Viana; M. Daffanio Wardhana; M. Syaidul Irfan Gunawan; M. Jauharul Fattah (Jurnal Informasi Pengabdian Masyarakat, 2025)
In line with the rapid advancement of Science and Technology (IPTEK), businesses are also required to keep pace with these developments, one of which is in the realm of rebranding and product marketing through internet-based media such as websites, Facebook, Instagram, Shopee, TikTok, and other social media platforms. The Community Service Program (PPM) of the KKN UNISNU Jepara Team, Batch XVIII, 2025, has been implemented in Ujungwatu Village, Donorojo District, Jepara Regency, with the aim of assisting product rebranding through the creation of attractive packaging and website development, as well as digital marketing training to increase sales revenue. The research method used in this program is field observation to identify problems faced by partners. Additionally, digital marketing training was conducted through lecture methods, where the instructor explained directly how to create an e-commerce account on Shopee. The results of this program show that creating attractive packaging can increase consumer appeal and confidence in the product. Furthermore, website development and digital marketing training through Shopee e-commerce can reach a wider market, thereby increasing sales revenue. Abstrak Program pengabdian masyarakat tim KKN UNISNU Jepara angkatan XVIII tahun 2025 dilaksanakan di Desa Ujungwatu, Kecamatan Donorojo, Kabupaten Jepara. Pada saat melakukan observasi, peneliti mengunjungi beberapa produsen usaha rumahan dan peneliti tertarik pada produsen Barokah Jaya untuk dijadikan sarana program pengabdian berbasis kemitraan. Usaha ini bergerak pada bidang pengolahan makanan berupa ikan bandeng. Berdasarkan analisis situasi pada saat Tim KKN melakukan observasi, Tim menemukan beberapa masalah yang di alami oleh mitra diantaranya yaitu kemasan produk dan proses pemasaran. Berdasarkan permasalahan yang di alami oleh rumah produksi Barokah Jaya, terdapat beberapa solusi yang bisa di lakukan yakni : Pertama, memberikan pemahaman mengenai pentingnya personal branding dalam suatu produk melalui kemasannya. Kedua, mengadakan pelatihan digital marketing, pendampingan tentang pengelolaan situs jual beli online dan pembuatan website commerce agar produk dapat dikenal oleh kalangan luas, sehingga dalam produksi ini mampu bersaing dengan usaha industri rumahan lainnya.